Erythroid Kruppel-like factor (EKLF) is recruited to the γ-globin gene promoter as a co-activator and is required for γ-globin gene induction by short-chain fatty acid derivatives - Perrine, Susan P. (2009)
OBJECTIVES: The erythroid Kruppel-like factor (EKLF) is an essential transcription factor for β-type globin gene switching, and specifically activates transcription of the adult β-globin gene promoter. We sought to determine if EKLF is also required for activation of the γ-globin gene by short-chain fatty acid (SCFA) derivatives, which are now entering clinical trials. METHODS: The functional and physical interaction of EKLF and co-regulatory molecules with the endogenous human globin gene promoters was studied in primary human erythroid progenitors and cell lines, using chromatin immunoprecipitation (ChIP) assays and genetic manipulation of the levels of EKLF and co-regulators. RESULTS AND CONCLUSIONS: Knockdown of EKLF prevents SCFA-induced expression of the γ-globin promoter in a stably expressed μLCRβ(pr)R(luc)(A)γ(pr)F(luc) cassette, and prevents induction of the endogenous γ-globin gene in primary human erythroid progenitors. EKLF is actively recruited to endogenous γ-globin gene promoters after exposure of primary human erythroid progenitors, and murine hematopoietic cell lines, to SCFA derivatives. The core ATPase BRG1 subunit of the human SWI/WNF complex, a ubiquitous multimeric complex that regulates gene expression by remodeling nucleosomal structure, is also required for γ-globin gene induction by SCFA derivatives. BRG1 is actively recruited to the endogenous γ-globin promoter of primary human erythroid progenitors by exposure to SCFA derivatives, and this recruitment is dependent upon the presence of EKLF. These findings demonstrate that EKLF, and the co-activator BRG1, previously demonstrated to be required for definitive or adult erythropoietic patterns of globin gene expression, are co-opted by SCFA derivatives to activate the fetal globin genes.